Análise comparativa na influência da técnica de moldagem funcional em arcos parcialmente edêntulos sobre os pontos de contato oclusais, a integridade da fibromucosa e a extensão da base da prótese - Dias, Kássia de Carvalho (2012)
There is a lack of clinical studies evaluating techniques of functional impression for partially edentulous arches. The aim of this double-blind non-randomized controlled clinical trial was to compare the efficacy of altered cast impression (ACI) and direct functional impression (DFI) techniques. The efficacy was evaluated regarding the number of occlusal units on denture teeth, mucosa integrity at 24-hour follow-up and denture base extension. The sample included 51 patients (female and male) with mean age of 58.96 years treated at Dental Department of UFRN. The patients, exhibiting edentulous maxilla and mandibular Kennedy class I, were divided into two groups (group ACI, n=29; group DFI, n=22). Clinical evaluation was based on the number of occlusal units on natural and/or artificial teeth, mucosa integrity at 24-hour follow-up, and denture base extension. Statistical analysis was conducted using the software SPSS 17.0® (SPSS Inc., Chicago, Illinois). Student T-test was used to reveal association between number of occlusal units and impression technique while chi-square test showed association between mucosa integrity and impression technique. Fischer s exact test was applied for association between denture base extension and impression technique at 95% level of significance. No significant difference was observed between the groups regarding number of occlusal units, mucosa integrity and denture base extension. The altered cast technique did not provide significant improvement in comparison to the direct technique when the number of occlusal units, mucosa integrity and denture base extension